Perbandingan Sistem Hukum Perlindungan Anak Antara Indonesia Dan Malaysia - Jauhari, Iman (Faculty of Sharia and Law - Sunan Kalijaga State Islamic University, 2013)
This paper aims to compare child protection law between Indonesiaand Malaysia especially in terms of family law (marriage), child definition andage limit, as well as other foundational principles. Content analysis method ofa variety of relevant references is used and a comparative approach to child protection law in Indonesia and Malaysia is taken. There are many similarities between child protection law in Malaysia and Indonesia, in which both systemsspecify the state, family, and parents responsibilities towards children. Alsospecified are handling of childs position, guardianship, rearing, adoption,religion, and abandonment. In addition, special protection such as maintenance,recovery, custody, care, investigation, nursing, education, prevention ofeconomic exploitation, prevention of sexual abuse, prevention of child torture,and disability treatment are also included. This paper concludes that in Malaysiachild protection law has been fully synthesised in Children Act of 2001 (Act611), while in Indonesia child protection law is scattered in a number of lawsrelated to children including the Child Protection Law.